2019
DOI: 10.1109/access.2019.2909070
|View full text |Cite
|
Sign up to set email alerts
|

Eight-Port MIMO Array Using Characteristic Mode Theory for 5G Smartphone Applications

Abstract: An 8-port multiple-input multiple-output (MIMO) array operating in the long-term evolution (LTE) band 42 (3400-3600 MHz) based on the characteristic mode theory (CMT) is described. As designing a multi-antenna system with multiple significant modes is difficult for the CMT, a new method is, therefore, proposed to effectively provide useful physical insights and improve the envelope correlation coefficient (ECC). Although many of the same modes are excited by two antennas, the proposed method is still effective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(59 citation statements)
references
References 28 publications
0
59
0
Order By: Relevance
“…With the allocation of the 3.5 GHz (3.4-3.6 GHz) band for 5G wireless communication [5], the sub-6 GHz MIMO antenna systems have been popularly studied to allow more antenna elements to be integrated into space-scarce terminal devices [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. It has been demonstrated that high isolation (i.e., low mutual coupling) and low correlation are essential figure-of-merits for MIMO antenna systems to guarantee excellent radiation performance and diversity property.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…With the allocation of the 3.5 GHz (3.4-3.6 GHz) band for 5G wireless communication [5], the sub-6 GHz MIMO antenna systems have been popularly studied to allow more antenna elements to be integrated into space-scarce terminal devices [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. It has been demonstrated that high isolation (i.e., low mutual coupling) and low correlation are essential figure-of-merits for MIMO antenna systems to guarantee excellent radiation performance and diversity property.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, the previously reported techniques for the sub-6 GHz 5G MIMO antennas can be categorized into the following two categories: decoupled MIMO antenna arrays by utilizing decoupling structures [6][7][8][9][10][11][12] and selfdecoupled MIMO antenna arrays without any additional structures [13][14][15][16][17][18][19][20][21][22][23]. For the decoupled MIMO antenna arrays, the frequently adopted decoupling structures include neutralization lines or decoupling networks [6][7][8][9], and additional resonators [9][10][11][12], which require additional occupation and complicated tuning efforts.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The characteristic mode analysis has attracted considerable attention in design and optimization of antennas [19]- [20], because it provides not only a clear physical insight into radiation behavior but also information of significant radiation modes that can be excited. It also has been applied for design and analysis of multiport networks such as antenna arrays [21], the metasurface resonator antennas [22], platform mounted antennas [23] and also aircraft-integrated multiband multiantenna systems [24]. However, to our best knowledge, few publications were presented on the frequency-selective surface design using the CM theory.…”
mentioning
confidence: 99%